Preventive Model and Legal Protection of Victims of Sexual Violence Crimes in Higher Education Environment - Alif Arhanda Putra; Karimah Syafiq (Lembaga Penelitian dan Pengabdian Masyarakat, 2022)
Preventive Model and Legal Protection of Victims of Sexual Violence Crimes in Higher Education. This study aimed to: analyze (i) preventive models of sexual violence crimes in higher education environment; and (ii) legal protection of victims of sexual violence crimes in higher education environment. This research uses a normative type of research, namely legal research methods to analyze the rule of law, legal principles, and legal doctrines to answer legal issues that are the subject matter of research. The types of research approaches are the statutory approach (The Statue Approach) and the conceptual approach (The Conceptual Approach). The technique of collecting materials is the study of documents and the study of literature. Prescriptively analyzed with deductive methods to answer the problems in this study. The results of this study show that: (i) Model prevents criminal acts of sexual violence committed by universities, educators, education staff, and students. Prevention through learning is carried out by leaders or leaders of universities by requiring students, educators, and education staff to study the sexual violence prevention and handling module set by the ministry; (ii) Legal protection for victims of sexual violence crimes in the university environment is the handling of sexual violence crimes carried out through mentoring, protection, imposition of administrative sanctions, and recovery of victims. Assistance carried out in the form of counseling, health services, legal assistance, advocacy, and/or social and spiritual guidance.